KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KEBIJAKAN LEVERAGE MELALUI PENDEKATAN KESEMPATAN BERTUMBUH DAN RISIKO PERUSAHAAN - Cliff Kohardinata; Christian Herdinata (University of Merdeka Malang, 2013)
The main purpose of company was to increase companys value through increased prosperity of owner orshareholders. However, the management often had other objectives that caused conflicts of interest betweenmanagement and shareholders of the company, in which the conflict was referred to as Agency Problem (Jensen Meckling, 1976). To minimize the differences between the interests of owners and managers, the owner couldgive shares to managers or increased stock ownership by institutional in order to monitor managers. If theowner of the company wanted to reduce agency conflicts by increasing managerial ownership and institutionalownership, they will affect corporate leverage policy because managerial ownership and institutional ownershipcould reduce the financial risk that occurred from leverage. This study aimed to analyze the effect ofmanagerial ownership and institutional ownership on leverage policy. This study used the entire populationof companies listed in Indonesia Stock Exchange. Sampling was purposive sampling, and analytical techniquesused was ordinary least squares. The control variables were structure of assets, return on assets, financialdistress, asset utilization, asset growth. Furthermore, this paper considered growth opportunities and risksof the company. This study found that managers considered risk factors more than growth opportunities, andthe institutional shareholders considered growth opportunities more than company risk